SNAILS COMPOSITION IN THE SOUTHERN PART OF GUNUNG HALIMUN NATIONAL PARK - Heryanto Heryanto (BERITA BIOLOGI, 2001)
Snails inventory in the southern part of Gunung Halimun National Park (GHNP) was conducted in two locations i.e., Ciptarasa and Simaresmi,in July and November 2000.It was found 36 species of snails that belongs to 16 families.It means that snails in the southern part of GHNP differs from that of the central part of the Park. Those snails were discovered in 9 habitat types.